Dynamic simulation of brake pedal force effect on heavy vehicle braking distance under wet road conditions - Zamzamzadeh, M.; Saifizul, A.A.; Ramli, R.; Soong, M.F. (Universiti Malaysia Pahang, 2016)
Recent experiences have shown that one of the main causes of heavy vehicle crashes is the braking performance. In particular, when having to decelerate in an emergency situation, such as when an unexpected object is in the road. Thus, the capability of a vehicle to come to a safe stop is one of the most important factors in preventing more accidents. Safe braking distance is influenced by many factors, such as brake pedal force, the vehicle's loading conditions, the travel speed and the road surface conditions. The aim of this study was to analyse the effect of the driver's brake pedal force on braking distance during an emergency situation, allowed for a wide range of heavy vehicle's GVW and speed. This study is carried out by using a multi-body dynamics simulation of a Single Unit Truck based on the validated vehicle model. Braking performance was estimated in terms of braking distance on a straight road with a wet surface. The findings from the braking distance simulation suggest a non-linear relationship between brake pedal force and braking distance. Finally, it reveals that, depending on the wheel lock-up situation, braking distance increases with increasing brake pedal force, and that the braking distance on a wet road is significantly affected by both the heavy vehicle's GVW and speed.